Kesederhanaan Beragama Menurut Hans Küng: Analisis dari Perspektif Islam: Moderation of Religion According to Hans Küng: An Analysis from Islamic Perspective - Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
The paper highlights the concept of moderation in religion by Hans Küng, a prominent theologian and inter-religious dialogue figure. He suggested two concepts that can be applied in religious life that are ‘self-criticism’ and ‘ecumenical criteria for truth’. According to Küng, both of these concepts are capable to form moderate religious perspective which do not constitute religious fanaticism and at the same time do not cause to religious principles being ignored. The study found that ‘self-criticism’ is meant a religious attitude, and ‘ecumenical criteria for truth’ is the criteria for determining the truth of a religion. By use of a qualitative approach, the paper analytically and critically examining two aspects described above from Islamic prespectives. As a conclusion, the concept of ‘moderation of religion’ as suggested by Küng otherwise produce inconsistency in religious belief. His ideas meets the secular humanism that laid the foundations of human subjectivity in the determination of absolute religious truth.